Innovation in the deliveryoh pharmaceutical care. - Jamil, Nurdiana; Zakaria, Syahiera Farhana (IIUM Press, 2011)
The concept of pharmaceutical care is the key foundation of modern-day patient-centered pharmacy services. Introduced in the late 1980's, the pharmaceutical care concept is the provision of medication-related therapy and for both preventive and treatment purposes with the ultimate purpose of improving patient's health status and quality of life (Helper & Strand, 1989; ASHP, 1993). The key principle of pharmaceutical care involves the direct delivery of medicationrelated therapy and care for the attainment of specific pre-defined outcomes by a pharmacist that has full commitment and full acceptance of responsibility and accountability. The elements of pharmaceutical care are outlined in Table 1.